Does Commitment to Home Organization Hurt the Inner Quality of Internal Auditors? Quadratic-Moderating Analysis - Sumarlin, Sumarlin (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
Public administration in the developing region is not always straightforward, e.g., in Indonesia. The workers are expected to display a high commitment to the organization; however, a particular role, like internal auditors, is in a constant tug-of-war as to following the top command or performing an independent assessment with solid integrity. This study advances the elusive conversation by portraying this phenomenon in Indonesia’s Islamic State University governance. This study records 137 responses from internal auditors and employs a PLS-SEM in the analysis. The finding reveals the most acceptance of the proposed hypotheses unless the quadratic effects of independence and integrity exist. Good university governance understanding decreases the over-commitment to the organization that may derail the auditors’ independence.